VacA genotypes and cagA‐EPIYA‐C motifs of Helicobacter pylori and gastric histopathological lesions. Issue 11 (6th July 2020) - El Khadir, Mounia; Boukhris Alaoui, Samia; Benajah, Dafr‐Allah; Ibrahimi, Sidi Adil; Chbani, Laila; El Abkari, Mohamed; Bennani, Bahia
Abstract: Helicobacter pylori infection induces inflammation of the gastric mucosa, which may progress to precancerous lesions and gastric cancer. The gastric histo‐pathological damages may be associated with some virulence genes of the bacterium, notably vacA and cagA genes. To establish correlations between these genes and the lesions, biopsies from 1303 adults consenting patients that were previously analyzed by PCR to characterize vacA ‐s vacA‐m, vacA‐i regions and cagA 3′ region polymorphism, were used. The highest average age was obtained in patients with intestinal metaplasia (53.65 ± 15.26 years) and gastric cancer (53.60 ± 14.32 years). Thus, these lesions are more frequent in elderly and male subjects. Tobacco smoking was significantly associated with neutrophilic activity ( P = .02). No significant association was obtained between patients with chronic inflammation and vacA and cagA H. pylori genotypes. However, a significant association has been obtained between this lesion and cagA + in aged patients ( P = .02), while intestinal metaplasia was significantly associated with vacAi1 and vacAm1 separately ( P  < .01 and .01). Also, a significant association was obtained between intestinal metaplasia and strains with one EPIYA‐C motif in young patients ( P = .001). Interestingly, a significant association was obtained between gastric cancer and cagA +, vacAi1, vacAm1 H. pylori genotypes and also with two EPIYA‐C motifs independently of age groups (all P  < .05). The results of our study show that H. pylori vacAi1 could be more potent than the other H. pylori virulent factors for predicting the precancerous gastric lesions, confirming that this gene may be helpful to identify patients at high risk for gastric cancer. What's new?: Progression of Helicobacter pylori infection from gastritis to gastric cancer (GC) likely is driven in part by polymorphisms in the bacterial virulence genes vacA and cagA . The association of these genes with H. pylori pathology, however, remains uncertain. Here, histological and molecular analyses of gastric tissue from patients in Morocco reveal significant associations between vacAi1, vacAm1, and cagA+ H. pylori genotypes and GC. GC risk was increased particularly in patients carrying H. pylori strains harboring two EPIYA‐C motifs. The data further indicate that vacAi1 predicts progression to GC and may be of clinical relevance in patients with H. pylori infection.